Perancangan Racecourse Berbasis Arsitektur Bioklimatik: Studi Penerapan Orientasi Bangunan dan Penghawaan Alami - Adwin, Muhammad Mahdi; Marwati, Marwati; Rahim, Rahmiani (TIMPALAJA : Architecture Student Journals, 2025)
A racecourse is a horse racing arena that holds significant local cultural value, such as the Palumba Jarang tradition in the Jeneponto community. However, the tropical climate in Jeneponto, characterized by high solar radiation and strong winds, poses a significant challenge, as it leads to higher temperatures in the racecourse area and reduces user comfort. This study aims to develop an architectural design that responds to the local climate through a bioclimatic approach, focusing on building orientation relative to sun and wind patterns, and on the application of natural ventilation to reduce heat and maximize air circulation. The research methodology includes analyzing local climate data, conducting design simulations, and applying bioclimatic principles, such as building layout arrangements, window designs, and adaptive building envelopes. The findings show that optimal building orientation relative to the sun and wind can reduce the impact of high temperatures, while opening designs that support natural ventilation and adaptive building envelopes can enhance air circulation and create a cooler environment. Therefore, this study emphasizes the importance of a bioclimatic approach that considers the relationship between building form, the surrounding environment, and local climate conditions, resulting in a climate-friendly racecourse design that fully aligns with bioclimatic architectural principles for tropical regions